Field- and laboratory-derived power-cadence profiles in world-class and elite track sprint cyclists - Wackwitz, T.; Minahan, C.; Menaspà, P.; Crampton, M.; Bellinger, P. (Journal of Sports Sciences, 2023)
Previous investigations comparing Torque-Cadence (T-C) and Power-Cadence (P-C) profiles derived from seated and standing positions and field and laboratory conditions are not congruent with current methodological recommendations. Consequently, the aim of this investigation was to compare seated and standing T-C and P-C profiles generated from field and laboratory testing. Thirteen world-class and elite track sprint cyclists (n = 7 males, maximal power output (Pmax) = 2112 ± 395 W; n = 6 females, Pmax = 1223 ± 102 W) completed two testing sessions in which field- and laboratory-derived T-C and P-C profiles were identified. Standing P-C profiles had significantly (p < 0.05) greater Pmax than seated profiles, however there were no significant differences in optimal cadence (Fopt) between seated and standing positions. Pmax and Fopt were significantly lower in field-derived profiles in both positions compared to laboratory-derived profiles. However, there was no significant difference in the goodness-of-fit (R2) of the P-C profiles between laboratory (0.985 ± 0.02) and field-testing (0.982 ± 0.02) in each position. Valid T-C and P-C profiles can be constructed from field and laboratory protocols; however, the mechanical variables derived from the seated and standing and field and laboratory profiles cannot be used interchangeably. Both field and laboratory-derived profiles provide meaningful information and provide complementary insights into cyclists` capacity to produce power output.